Goodbye to Berlin - Isherwood, Christopher, 1904-1986 (New Directions paperbook, 2012)
"First published in 1934, Goodbye to Berlin has been popularized on stage and screen by Julie Harris in I Am a Camera and Liza Minelli in Cabaret. Isherwood magnificently captures 1931 Berlin: charming, with its avenues and cafés; marvelously grotesque, with its nightlife and dreamers; dangerous, with its vice and intrigue; powerful and seedy, with its mobs and millionaires ? this was the period when Hitler was beginning his move to power. Goodbye to Berlin is inhabited by a wealth of characters: the unforgettable and ?divinely decadent? Sally Bowles; plump Fraulein Schroeder, who considers reducing her Buste to relieve her heart palpitations; Peter and Otto, a gay couple struggling to come to terms with their relationship; and the distinguished and doomed Jewish family, the Landauers."--back cover.